Community Managed Forest Groups and Preferences for REDD+ Contract Attributes : A Choice Experiment Survey of Communities in Nepal - Dissanayake, Sahan T. M.; Jha, Prakash; Adhikari, Bhim; Bista, Rajesh; Bluffstone, Randall; Luintel, Harisharan; Martinsson, Peter; Paudel, Naya Sharma; Somanathan, E.; Toman, Michael (World Bank, Washington, DC, 2015)
A significant portion of the world’s forests that are eligible for Reducing Emission from Deforestation and Forest Degradation, known as REDD , payments are community managed forests. However, there is little knowledge about preferences of households living in community managed forests for REDD contracts, or the opportunity costs of accepting REDD contracts for these communities. This paper uses a choice experiment survey of rural communities in Nepal to understand respondents’ preferences toward the institutional structure of REDD contracts. The sample is split across communities with community managed forests groups and those without community managed forest groups to see how prior involvement in community managed forest groups affects preferences. The results show that respondents care about how the payments are divided between households and communities, the severity of restrictions on firewood use, the restrictions on grazing, and the fairness of access to community managed forest resources as well as the level of payments. The preferences for REDD contracts are in general similar between community managed and non-community managed forest resource respondents, but there are differences, in particular with regard to how beliefs influence the likelihood of accepting the contracts. Finally, the paper finds that the opportunity cost of REDD payments, although cheaper than many other carbon dioxide abatement options, is higher than previously suggested in the literature.